Gagal Mengikat Tinggi-Heron-Relasi Sisi : Analisis Miskonsepsi Mahasiswa pada Segitiga - Lutfiyah Lutfiyah; Susanto Susanto; Abi Suwito; Frenza Fairuz Firmansyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to identify and describe in depth the emergence of conceptual misconceptions and procedural errors, as well as the dynamics of students' thinking processes when solving triangle geometry problems. The research used a descriptive qualitative approach with a case study design on three mathematics education students who had taken basic geometry, selected purposively to represent a variety of academic abilities and allow for intensive exploration of thought processes. The instrument is a triangular geometry problem solving task that looks for height, area, and lateral relations. Data was collected through written answer sheets, video recordings of the work, and retrospective clarification interviews, then analyzed qualitatively to trace patterns of misconceptions and procedural errors in the problem-solving flow. Data validity through source triangulation and trail auditing. The results showed that the three students displayed a neat calculation procedure, but were conceptually fragile. The height of a triangle is not interpreted as a perpendicular relation, the use of the theorem is carried out without prerequisites, and the relations between the lateral segments are assumed intuitively. Weak monitoring and evaluation during the problem-solving process hinders the formation of a coherent conceptual framework. These findings confirm the need for geometry learning that emphasizes the status of mathematical objects, adherence to the prerequisites of concepts and theorems, and the development of reflective monitoring habits in problem solving.